Kepemimpinan Spiritual Kepala Sekolah Dalam Meningkatkan Budaya Religius Siswa di SMA Sunan Kalijogo Jabung Malang - At-Turmudzi, Aufa Husna Aulia; Anwar, Khoirul (CV. Satria Jaya, 2025)
Leadership and spirituality are closely related, recalling that humans are caliphs on earth, however, how high the level of spirituality is is not the same. Researchers are interested in studying because in their journey leadership has a spirit in the name of God. The interrelationship of students' religious culture in schools. So connected with the spiritual leadership of the school principal in instilling religious culture in students, so the research title was born